P-glycoprotein expression and distribution in the rat placenta during pregnancy - Novotna, Martina; Libra, Antonin; Kopecky, Martin; Pavek, Petr; Fendrich, Zdenek; Semecky, Vladimir; Staud, Frantisek (Reproductive toxicology (Elmsford, N.Y.), 2004)
P-glycoprotein (P-gp) is a drug efflux transporter that limits the entry of various potentially toxic drugs and xenobiotics into the fetus and is thus considered a placental protective mechanism. In this study, P-gp expression was investigated in the rat chorioallantoic placenta over the course of pregnancy. Three methods have been employed: real-time RT-PCR, western blotting and immunohistochemistry. The expression of mdr1a and mdr1b genes was demonstrated as early as on the 11th gestation day (gd) and increased with advancing gestation. Western blotting analysis revealed the presence of P-gp in the rat placenta starting from gd 13 onwards. P-gp was localized in the developing labyrinth zone of the placenta on gd 13; from gd 15 up to the term P-gp was seen as a dot like continuous line in the syncytiotrophoblast layers. Our data confirm the presence of P-gp in the rat chorioallantoic placenta starting soon after its development, which may signify the involvement of P-gp in transplacental pharmacokinetics during the whole period of placental maturing.
Keywords: ATP-Binding Cassette Transporters; Animals; Female; Rats, Wistar; Chorion; Blotting, Western; ženské pohlaví; ABC transportér, podrodina B, člen 4; těhotenství u zvířat; Antibodies, Monoclonal; Immunohistochemistry; placentace; Placenta; ABC transportéry; P-glykoprotein; ATP Binding Cassette Transporter, Subfamily B; těhotenství; ATP Binding Cassette Transporter, Subfamily B, Member 1; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; ATP-Binding Cassette Sub-Family B Member 4; imunohistochemie; RNA, Messenger; P-glykoproteiny; western blotting; Membranes; Placentation; Reverse Transcriptase Polymerase Chain Reaction; chorion; krysa rodu Rattus; monoklonální protilátky; Pregnancy, Animal; zvířata; Pregnancy; placenta; Rats; membrány; potkani Wistar